A novel mutation in GAS8 gene associated with chronic rhinosinusitis with nasal polyposis in a case of primary ciliary dyskinesia: a case report - Artesani, Maria Cristina; Santarsiero, Sara; Sitzia, Emanuela; Lepri, Francesca Romana; Magliozzi, Monia; Majo, Fabio; Ullmann, Nicola; Stracuzzi, Alessandra; Novelli, Antonio; Cristalli, Giovanni; Fiocchi, Alessandro (Frontiers in Pediatrics, 2024)
Background Primary ciliary dyskinesia (PCD) is considered a rare cause of chronic rhinosinusitis with nasal polyposis (CRSwNP) which is reported in 6% of PCD children. The forms of PCD associated with the variants of the GAS8 gene identified so far seem to be linked to recurrent respiratory infections (sinusitis, otitis, and bronchiectasis) without situs inversus. Case presentation We report a case of an eleven-year-old girl with recurrent otitis media, productive cough and chronic rhinosinusitis with nasal polyposis with homozygosity for a novel nonsense mutation in the GAS8. Conclusion Children with CRSwNP should be treated in a multidisciplinary way (ENT, pulmonologist, allergist, pathologist, paediatrician and geneticist) because nasal polyposis often hides aetiologies that must be recognized.